A detoxified TLR4 agonist inhibits tumour growth and lung metastasis of osteosarcoma by promoting CD8+ cytotoxic lymphocyte infiltration - Ryunosuke Oyama; Akira Nabeshima; Makoto Endo; Alexey Novikov; Toshifumi Fujiwara; Capucine Phelip; Nobuhiko Yokoyama; Yoshinao Oda; Martine Caroff; Yoshihiro Matsumoto; Jerome Kerzerho; Yasuharu Nakashima (BJC Reports)
Abstract Background Osteosarcoma is the most common malignant bone tumour with limited treatment options and poor outcomes in advanced metastatic cases. Current immunotherapies show limited efficacy, highlighting the need for novel therapeutic approaches. Systemic immune activation by Toll-like receptor 4 (TLR4) immunostimulants has shown great promise; however, current TLR4 agonists’ toxicity hinders this systemic approach in patients with osteosarcoma. Methods We compared the antitumour effect of lipopolysaccharides (LPS) with that of an innovative chemically detoxified TLR4 agonist (Lipo-MP-LPS) in a syngeneic metastatic osteosarcoma mouse model. Lipo-MP-LPS exhibited an optimal safety and solubility profile for systemic administration at an effective dose. We evaluated tumour growth, lung metastases, and immune cell infiltration in wild-type and TLR4-mutant mice and performed selective immunodepletion. Results Lipo-MP-LPS exhibited antitumour effects against localised osteosarcoma tumours and lung metastases, like those of natural LPS. Lipo-MP-LPS promoted CD8+ T cells and M1 macrophages infiltration in primary tumours and CD8+ T cells in metastases, with an M1-phenotype macrophage shift. The Lipo-MP-LPS antitumour effects were found to depend on TLR4 and CD8+ T cells, but not on macrophages. Conclusion Lipo-MP-LPS inhibited tumour growth and lung metastasis of osteosarcoma by promoting CD8 + T cell infiltration, indicating its therapeutic potential for advanced osteosarcoma.